Tingginya Jujuran dalam Pernikahan di Desa Lokdalam Kecamatan Angkinang Kabupaten Hulu Sungai Selatan Kalimantan Selatan - Ramadhani, Muhammad Rafiq; Rinaldi, Muhammad Naufal; Hilyati, Anita; Safitri, Adellia Essa; Fatimah, Eva Nor; Efendy, Noor (Sharia Journal and Education Center Publishing, 2024)
In marriage, the Banjar community distinguishes between dowry and jujuran. The dowry is an obligation given by the husband to the wife in an Islamic marriage, while the jujuran is a gift that must be given by the man to the woman in Banjar custom. The level of jujuran usually varies, which makes it interesting to analyze it further. How the community views the jujuran, what are the factors that influence the high jujuran and what are the impacts of the high jujuran. The purpose of this study is to determine the community's view of jujuran, the factors that influence the high and low jujuran and the impact of high jujuran in Lokdalam Village. The research used is field study research with qualitative methods. This research found that the community views dowry and jujuran as different, but there are also those who view them the same. In determining the jujuran based on deliberation from both parties. The jujuran money is used for the needs of the reception event but some are also saved. The average price of jujuran in Lokdalam Village is 40-60 million. The factors that most influence the high price of jujuran are education, social status, and expertise/employment. Meanwhile, factors that rarely influence the jujuran are parents or family factors, beauty factors. The positive impact of high jujuran is that it makes family relationships closer, can see the seriousness of the man and the man becomes motivated to work harder to legalize his idol. The negative impact can cause damage to family relationships, delayed marriage and even not getting married because the jujuran is too high and the jujuran is not suitable.